Update of the Regional Strategy of Rural Youth in Central American Integration System (SICA) Region - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
CCAFS informed the update of the Rural Youth Strategy by developing a gender-based analysis of the impacts of COVID-19 in rural youths of SICA.